Smart Production Planning: Presenting a Framework for the Importance and Application of Features of the Production Planning Environment (Case Study: Pharmaceutical Industry) - Salimi Zaviyeh, Seyed Ghasem; Kazazi, Abolfazl; Raeesi Vanani, Iman; Ghazinoori, Soroush (Management Strategies and Engineering Sciences, 2024)
The purpose of this paper was to examine the importance of smart production planning for improving performance, considering the specific features of the planning environment in the pharmaceutical industry. This study uses four empirical case studies in the pharmaceutical industry. These four cases represent four companies producing different products within the pharmaceutical industry for various markets, each with distinct processes. Additionally, along with industry insights, these frameworks were used to identify, define, and structure the variables expected to have the greatest impact on the importance of smart production planning within the theoretical framework. This work was carried out through discussions within the project team and repeated multiple times. The framework was subsequently used to map and analyze the four empirical case studies in the biopharmaceutical pharmaceutical industry. The cases were selected to demonstrate different features of the planning environment and smart production planning approaches, ranging from make-to-stock (MTS) to assemble-to-order (ATO) and make-to-order (MTO). Data was collected through observations and site visits at pharmaceutical manufacturing facilities, workshops, consultations, and formal interviews with production managers, production planners, smart supply chain managers, innovation managers, and production line engineers. Internal and cross-case analyses were performed through several iterations within the pharmaceutical industry team. The fundamental finding is that the potential and importance of smart production planning for improving performance increase with the complexity of the production planning environment. As a result, nine final steps for the design and development of smart production planning importance are presented. The conceptual framework presented is based on the combination of smart production planning, the features of the production planning environment, and the elements of the Fourth Industrial Revolution. The developed framework serves two objectives. First, it provides a tool to structure and describe the planning environment in the pharmaceutical industry, considering product, market, and process features. Insights gained from such a framework regarding the planning environment's features can be useful for smart production purposes. The second contribution of the framework is linking the planning environment's features with smart production planning. The core logic is that the importance of smart production planning for improving performance increases with the intelligence and complexity of the planning environment.